Rolul caselor de ajutor reciproc ale pensionarilor în cadrul dezvoltării locale - Stănilă, Gabriel (Calitatea Vieții, 2013)
The role of this paper is to present and examine the role that mutual aid’s associations of pensioners play in local development process in Romania. The type of services provided by the mutual aid’s associations of pensioners, the effects thereof on the community, determine the major role such entities play within the local development process. This paper presents a qualitative analysis of two entities, Mutual aid’s association of pensioners from Ramnicu Valcea and Mutual aid’s association of pensioners from Targu Neamt. Both entities were included in the sample of research conducted in Romania by the team of the project “Prometeus – Promoting social economy in Romania through research, education and training at European standards”. The purpose of this analysis is to show how the activities of such entities can solve the problems of it’s members, and to demonstrate that this kind of entities follows the principles of social economy. The analysis was performed by following two directions: work and the principles of social economy. Regarding work, great emphasis was placed on the number of members, loan type and range of services offered to them (free or subsidized price). In accord to the principles of social economy, both entities, through the statute of each of these organizations and through respecting the EMES indicators: social objective, participatory, distribution of profits, decisions made democratically. The mutual aid’s associations of pensioners are, in most of the cases, the engine of the local development, through the activities which they develop. The characteristics of these entities – the non-profit character, the social purpose of the activity, the participation of the members in the government, the multistakeholders governance – allow these organizations to mobilize local resources, to stimulate the creation of social capital at the level of the community, to ensure the welfare of the members of the community. In the same time, mutual aid’s associations of pensioners facilitates financial inclusion by members that provide access to loans elderly, persons whose income and age prevents them from accessing a loan from a commercial bank.